Comparison of Scab Warning Systems in Integrated Apple Production - Holb, Imre (Acta Agraria Debreceniensis, 2003)
In the present study, the suggestions for infection risk and sprays of the most frequently used PC-based scab warning systems (RIMpro and WELTE) and the conventionally used Mills table as a reference were compared in integrated apple production. The efficacy of the spraying programs based on the three different warning systems was evaluated by assessment of apple scab incidences during primary infection periods.13 and 11 Mills infection periods were detected in 2000 and 2001, respectively, during primary infection periods (from 15 March until 5 June). Taking into consideration the heaviness of Mills infection periods, 11 and 9 sprays were applied in 2000 and 2001, respectively. The two PC-based scab warning systems detected 1-4 less infection periods and suggested 1-3 less sprayings compared to the numbers of infection periods and sprays according to the Mills table. Our results proved that the 9-11 sprays according to the Mills table could be reduced to 7-9 sprays by RIMpro scab warning systems which did not reduce the efficacy and did not increase the symptoms of leaf and fruit scab significantly. The WELTE scab warning systems detected generally one or two more infection periods and suggested one additional spray compared to RIMpro warnings and sprays.